THE NOTION OF LINGUISTIC WORLD PICTURE" AS A LINGUISTIC PROBLEM - Bisenova Aygerim (Journals Park Publishing, 2024)
This article explores the concept of the "world picture," a central notion in understanding human cognition and perception, and the role of language in shaping it. The world picture represents a structured system of knowledge about reality, influenced by cultural, historical, and cognitive factors. Language, as both a tool of perception and communication, plays a pivotal role in forming what is known as the "linguistic world picture," a verbal representation of the conceptual world picture. Additionally, it highlights the functional roles of the linguistic world picture - interpretative, regulative, nominative, identifying, and sociocultural. The article concludes by underscoring the dynamic interaction between the conceptual and linguistic world pictures and their significance in the broader context of human sciences, including linguistics, cultural studies, and psychology.
Keywords: world picture, concept, linguistic picture, cognition, human mind.